Effect of replacing alfalfa hay with wheat silage on growth performance, nutrient digestibility, ruminal fermentation, and serum metabolites in feedlotting lambs - H. Chen; Y. Jiang; W. Li; Z. Cui; Z. Cao; H. Yang (Animal)
This study investigated the potential of using wheat silage (WS) as a partial or complete replacement for alfalfa hay (AH) in the diets of feedlotting lambs, addressing the global challenge of high feed costs and forage scarcity in livestock production. Wheat silage is widely cultivated across many regions, making it a practical and cost-effective alternative to alfalfa hay, particularly in areas where alfalfa is expensive or scarce. Sixty-four male small-tailed Chinese Han lambs with similar BWs (15.6 ± 0.41 kg) were selected and divided into four treatment diets according to the proportion of wheat silage replacing alfalfa hay:WS0 (WS: AH = 0: 100), WS36 (WS: AH = 36: 64), WS64 (WS: AH = 64: 36), and WS100 (WS: AH = 100: 0). Forage to concentrate ratios were fixed at (25:75) during Stage 1 (lambs aged 2–4 months) and (20:80) during Stage 2 (lambs aged 4–6 months). Results demonstrated that the digestibilities of ADF and NDF were greater (P < 0.01) in both WS36 and WS64 than in the WS100 group during Stage 1, and no significant differences were observed between the WS0 and WS100 groups. However, during Stage 2, the digestibility of both ADF and NDF was significantly lower in the WS100 group compared to the other three treatments. In terms of growth performance, the WS36 group had the greatest final BW in both stages. Ruminal pH and the molar propionate percentage decreased linearly with the increase of WS inclusion, while the molar acetate percentage and acetate: propionate ratio increased linearly with the increase of WS inclusion in both stages. However, the concentration of ammonia nitrogen, microbial CP, and total volatile fatty acids in the rumen showed a significant linear decrease in Stage 2. Among serum metabolism indexes, the insulin-like growth factor-1 decreased linearly (P < 0.01), while creatinine increased linearly with the increasing WS inclusion (P < 0.01). Meanwhile, serum total protein tends to decrease linearly in Stage 2 (P < 0.01). These findings highlight the international relevance of wheat silage as a sustainable forage alternative in intensive livestock systems worldwide. In summary, feeding a total mixed ration containing 36% wheat silage instead of alfalfa hay improved growth performance and nutrient digestibility, offering a viable solution for sustainable lamb production globally.